Postmodernisme et hybridation chez Maurice G. Dantec - Isabelle Périer (ReS Futurae, 2013)
Maurice G. Dantec’s work takes part in the legacy of the cyberpunk’s pioneers and yet breaks up from it in many ways. On the one hand, it also claims to stem from literature, which shows through a celebration of the powers of language and through narrative and stylistic achievement. On the other hand, it goes deeper into the postmodern hybridation between pop culture and “high” culture and technology and transcendence, clearly shifting the latter towards christianism, thus attempting to shape a new narrative of trancendence.